2019
DOI: 10.5935/1984-0063.20190076
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent influence of gender on symptoms of obstructive sleep apnea in adults

Abstract: ObjectiveObstructive Sleep Apnea (OSA) is linked to classical symptoms of snoring and excessive sleepiness. However, many women with OSA may present with a diverse profile. The influence of age on the clinical differences between genders is unclear. This survey aimed to compare the clinical and polysomnographic findings of OSA between adult males and females, but considering different age groups. MethodsThis cross-sectional study comprised a sample of 472 consecutive adult patients with OSA who underwent full-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Males were 55.41 ± 11.24 years old on average, and females were 52.11 ± 3.12 years old ( Table 1 ). An earlier study found that men and people between the ages of 30–64 are more likely than women to suffer from OSA [ 18 ]. Another study found that people between the ages of 30 and 60 are more likely to experience respiratory problems when they sleep [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Males were 55.41 ± 11.24 years old on average, and females were 52.11 ± 3.12 years old ( Table 1 ). An earlier study found that men and people between the ages of 30–64 are more likely than women to suffer from OSA [ 18 ]. Another study found that people between the ages of 30 and 60 are more likely to experience respiratory problems when they sleep [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to male patients, female patients seem to have less severe OSA with lower overall Apnea-Hypopnea Index (AHI) in all ages, shorter apneic episodes, less severe oxygen desaturations, lower proportion of supine OSA, and more clustering of apneas during rapid eye movement sleep despite being older and more obese [30, 32, 34, 35]. However, it is important to point out that despite less severe OSA in terms of AHI, female patients are not less symptomatic compared to males and report sleepiness at relatively low levels of AHI [36]. Furthermore, severity of OSA increases in both genders with age, but the difference in AHI between female and male patients decreases after the age of 60–62 years [30, 37].…”
Section: Methodsmentioning
confidence: 99%
“…In general, male have more severe OSA and female have less severe symptoms at all ages. 9) Male OSA patients complain more commonly of classic symptoms, such as sleepiness, snoring, or witnessed apnea. However, female OSA patients complain of atypical symptoms, such as insomnia or morning headache.…”
Section: Age Adjusted Sex Differences In Clinical Features Of Korean ...mentioning
confidence: 99%